Discovery of topological Weyl fermion lines and drumhead surface states in a room temperature magnet - Belopolski, Ilya; Manna, Kaustuv; Sanchez, Daniel S.; Chang, Guoqing; Ernst, Benedikt; Yin, Jiaxin; Zhang, Songtian S.; Cochran, Tyler; Shumiya, Nana; Zheng, Hao; Singh, Bahadur; Bian, Guang; et al. (Science, 2019)
Topological matter is known to exhibit unconventional surface states and anomalous transport owing to unusual bulk electronic topology. In this study, we use photoemission spectroscopy and quantum transport to elucidate the topology of the room temperature magnet Co2MnGa. We observe sharp bulk Weyl fermion line dispersions indicative of nontrivial topological invariants present in the magnetic phase. On the surface of the magnet, we observe electronic wave functions that take the form of drumheads, enabling us to directly visualize the crucial components of the bulk-boundary topological correspondence. By considering the Berry curvature field associated with the observed topological Weyl fermion lines, we quantitatively account for the giant anomalous Hall response observed in this magnet. Our experimental results suggest a rich interplay of strongly interacting electrons and topology in quantum matter.
CRIS-Team Scopus Importer:2022-04-14